Environmental, social, and governance performance and corporate bond ratings: empirical evidence from Indonesia - Widialestari Rahayuningtyas; Khairunnisa Khairunnisa (Indonesia Auditing Research Journal, 2026)
This study examined the influence of Environmental, Social, and Governance (ESG) performance on corporate bond ratings among companies listed on the Indonesia Stock Exchange during the 2020–2024 period. A quantitative approach was employed using secondary data obtained from Refinitiv, PT Pemeringkat Efek Indonesia (PEFINDO), annual reports, and sustainability reports. The sample consisted of 23 companies with 106 firm-year observations selected through purposive sampling. Binary logistic regression was used to test the proposed relationships. The results showed that Total ESG Score and Environmental performance did not significantly affect corporate bond ratings. In contrast, Social performance had a positive and significant effect, while Governance performance exhibited a significant negative effect. Furthermore, the Environmental, Social, and Governance dimensions jointly influenced corporate bond ratings. These findings indicate that ESG dimensions contribute differently to credit assessments and that evaluating individual ESG dimensions provides more meaningful information than relying solely on an aggregate ESG score in explaining corporate bond ratings in Indonesia